Information Sharing and the Role of Sex Offender Registration and Notification, United States, 2009-2017 - Harris, Andrew J. ([Verlag nicht ermittelbar], 2021)
This study was conducted to evaluate and better improve inter-jurisdictional consistency and coordination of SORN (sex offender registration and notification) systems operating within the United States under SORNA (the Sex Offender Registration and Notification Act). The study examined the progress that has been made toward SORNA's goals as envisioned in 2006, with a particular emphasis on changes in information sharing over that period. The study utilized a mixed-method approach, including nationwide analyses of official data and a series of in-depth state case studies featuring interviews with 152 federal, state, and local personnel involved in various aspects of SORN operations and policy development across 10 states. Specific areas of focus included: 1) the nature, extent, and dynamics of state implementation of SORNA requirements; 2) the scope and evolution of information-sharing practices within the states, including both areas of success and challenge; and 3) the impacts of federal initiatives, including the expanded role of the US Marshal Service and information technology initiatives, on the achievement of SORNA's goals.